RADIOLARIAN BIOSTRATIGRAPHIC EVIDENCE FOR A LATE JURASSIC AGE OF THE EL TAMBOR GROUP OPHIOLITES (GUATEMALA) - Chiari, Marco; Dumitrica, Paulian; Marroni, Michele; Pandolfi, Luca; Principi, Gianfranco (Ofioliti, 2024)
We present a radiolarian biostratigraphic study of the metacherts of the El Tambor Group ophiolites (South Motagua Unit), Guatemala. The ophiolite sequence comprises MOR pillow metabasalts, massive metabasalts, metacherts and micaschists. The age of the studied metacherts is referable to the Late Jurassic (Oxfordian - Kimmeridgian).The radiolarian assemblage described in this paper is the first Jurassic finding in the ophiolitic MOR succession of the Motagua zone and represents a valuable tool to constrain the geodynamic evolution of the Caribbean area.A review of the ages of Jurassic rocks associated with the ophiolites from the Caribbean area is also reported.